Educational Equity in a Globalized Era: Comparative Insights from Southeast Asia and Other Developing Regions - Widaningsih; Rahman, Najib Aulia (Sinergi International Journal of Education, 2023)
Globalization continues to reshape education systems worldwide, compelling national governments to reassess and reform their educational policies. This study explores how globalization affects national education policy across social, economic, and governance dimensions. Using a systematic narrative review methodology, literature was collected from Scopus, PubMed, and Google Scholar using targeted keywords such as "globalization in education," "educational policy," and "academic mobility." Inclusion criteria focused on empirical and conceptual studies published between 2000 and 2024. The findings are organized around three primary social, economic, and policy-related factors. Social dynamics, including family structure and cultural values, significantly influence educational access and outcomes. Economic conditions such as household income and unemployment directly shape educational opportunities, while policy frameworks and international regulations determine how countries respond to global educational trends. The study highlights disparities between developed and developing countries in both policy implementation and outcomes. It also emphasizes the systemic barriers that hinder education reforms, including inadequate infrastructure, regulatory misalignments, and limited stakeholder participation. The discussion suggests that effective policy requires localization of global frameworks, inclusive governance, and investments in technology and equity. In conclusion, addressing these challenges demands coordinated action, context-aware policy adaptation, and further interdisciplinary research to enhance educational equity in a rapidly globalizing world.